Macrophages: plastic participants in the diagnosis and treatment of head and neck squamous cell carcinoma - Lin, Chen; Chu, Yidian; Zheng, Ye; Gu, Shanshan; Hu, Yanghao; He, Jiali; Shen, Zhisen (Frontiers in Immunology, 2024)
Head and neck squamous cell carcinoma (HNSCC) rank among the most prevalent types of head and neck cancer globally. Unfortunately, a significant number of patients receive their diagnoses at advanced stages, limiting the effectiveness of available treatments. The tumor microenvironment (TME) is a pivotal player in HNSCC development, with macrophages holding a central role. Macrophages demonstrate diverse functions within the TME, both inhibiting and facilitating cancer progression. M1 macrophages are characterized by their phagocytic and immune activities, while M2 macrophages tend to promote inflammation and immunosuppression. Striking a balance between these different polarization states is essential for maintaining overall health, yet in the context of tumors, M2 macrophages typically prevail. Recent efforts have been directed at controlling the polarization states of macrophages, paving the way for novel approaches to cancer treatment. Various drugs and immunotherapies, including innovative treatments based on macrophages like engineering macrophages and CAR-M cell therapy, have been developed. This article provides an overview of the roles played by macrophages in HNSCC, explores potential therapeutic targets and strategies, and presents fresh perspectives on the future of HNSCC treatment.